Discontinuation Patterns and Cost Avoidance of a Pharmacist-Driven Methicillin-Resistant Staphylococcus aureus Nasal Polymerase Chain Reaction Testing Protocol for De-escalation of Empiric Vancomycin for Suspected Pneumonia. (4th March 2021) - Meng, L; Pourali, S; Hitchcock, M M; Ha, D R; Mui, E; Alegria, W; Fox, E; Diep, C; Swayngim, R; Chang, A; Banaei, N; Deresinski, S; et al.
Abstract: A pharmacist-driven methicillin-resistant Staphylococcus aureus (MRSA) nasal polymerase chain reaction (PCR)-based testing protocol with a 70% acceptance rate for vancomycin discontinuation within 24 hours of negative results significantly reduced unnecessary vancomycin use with an estimated cost avoidance of $40 per vancomycin course. We found high concordance (141 of 147, 96%) of culture-based versus PCR-based MRSA nasal screening.